Flouting and hedging maxims in graduate students’ classroom discussion context - Aminah Aminah (ARKA INSTITUTE, 2022)
Effective communication is importance in avoiding misunderstanding and misinterpretation in our daily life including a discussion in classroom activity. Some flouting and hedging can be happened in a discussion. Hence, this research concerns to investigate how the conversational implicatures especially flouting and hedging maxim are being formed in students dialog during discussion class. This research is designed as descriptive research. The participants are students of LRM’S class which consist of 18 students that chosen by purposive sampling. The data was collected through tape recorder and interview. The data are being transcribed and analyzed by categorizing utterances based on the flouting of maxim and hedging maxim theory. Based on the data analysis, it has been discovered that during the conversation, whether they are presenters or participant in the discussion, they do flouting and hedging. Flouting maxim is frequently done than hedging maxim. Then, it happens for some reasons including want to give a right information, do not understand with the question, want to give a clear and relevance answer and want to build good relationship among students and lecturer. This study is wanted to raise people awareness toward flouting and hedging maxim in order to have an effective communication in life.